Compreendendo o goleiro na iniciação esportiva em handebol - Nassuato, Lucas [UNESP] (2017)
Sports initiation is the phase of the first contact of the child, adolescent, adult or elderly with sports, which can happen in different contexts (schools, clubs, social initiatives by the prefectures, among others). In this sense, teachers and coaches need to understand the complexity of the teaching and learning process through sport and offer incentives that allow students to experience the innumerable possibilities within a sporting modality. In some collective sports games (JEC), such as handball, it is possible to provide the experience of the role of goalkeeper, one of the positions that often ends up being forgotten during the initiation phase, compromising an important particularity of this moment of sports initiation. From this point of view, understanding the students when they try to play the role of goalkeeper is the first step in identifying the elements necessary for the planning of the classes, so the objective of the study was to investigate the behavior of the students when they assume the role of handball goalkeeper. It is a qualitative research with a descriptive-interpretative approach and the collection techniques used were: interviews with the students and observations through the filming of reduced handball games with 15 children and adolescents who participated in the project Teaching and Learning Handball offered by the Department of Physical Education of the Paulista State University Júlio de Mesquita Filho (UNESP) Campus of Bauru/São Paulo. The results show: fear of the ball, fear of making mistakes and preference to play in the attack as elements responsible for discouraging beginner students to play in the goal. We also identified the need for pedagogical interventions aimed at developing the tactical capacity of the apprentice of this specific position. We note that the why to do should always be more valued than the know-how during the sports initiation phase